Tissue sodium in patients with rheumatoid arthritis: a novel potential driver of hypertension in autoimmunity - Carolina Ramirez-Becerra; Annette M. Oeser; Michael Pridmore; Rachelle Crescenzi; Jens M. Titze; C. Michael Stein; Michelle J. Ormseth (Scientific Reports)
Abstract Patients with rheumatoid arthritis (RA) have increased hypertension. Tissue sodium may contribute to development and progression of hypertension through immune cell activation. This study aimed to determine if skin sodium content is: 1) higher in RA versus control participants, and 2) associated with blood pressure and disease activity. This cross-sectional study included 32 patients with RA and 33 control participants. Lower leg skin sodium content was measured using magnetic resonance imaging. Ambulatory 24-h blood pressure measurements were obtained, and disease activity was assessed by Disease Activity Score-28 for RA with CRP (DAS28-CRP). Skin sodium content was higher in RA versus control participants (14.22 [12.82, 18.04] vs 12.41 [10.67, 14.55] mmol/L), p = 0.005. Every 1 mmol/l increase in skin sodium was associated with a 1.05 mmHg (95% CI 0.29, 1.82 mmHg, p = 0.009) increase in average 24-h systolic blood pressure in patients with RA, but this relationship was not present in control participants. Skin sodium was not associated with DAS28-CRP or its components. Skin sodium is increased in RA versus control participants and is correlated with 24-h and diurnal systolic blood pressure in patients with RA but not in control participants. Skin sodium content may help explain increased hypertension in patients with RA.